2021
DOI: 10.1177/01650254211005560
|View full text |Cite
|
Sign up to set email alerts
|

Validation of motor, cognitive, language, and socio-emotional subscales using the Caregiver Reported Early Development Instruments: An application of multidimensional item factor analysis

Abstract: The Caregiver Reported Early Development Instruments (CREDI) are assessments tools for measuring the development of children under age three in global contexts. The present study describes the construction and psychometric properties of the motor, cognitive, language, and socio-emotional subscales from the CREDI’s long form. Multidimensional item factor analysis was employed, allowing indicators of child development to simultaneously load onto multiple factors representing distinct developmental domains. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…With regard to validity, multidimensional item factor analyses applied to the original multicountry validation sample revealed evidence of construct validity of the CREDI's long form. 11 In particular, a fourfactor model with item cross-loadings was found to be the best fit for the data. This work not only suggests that the CREDI is appropriately able to capture the four distinct but correlated domains of children's motor, language, cognitive, and social-emotional functioning but also demonstrates the broader utility of multidimensional scoring approaches that allow for the fact that young children's behaviors are often reflective of multiple underlying skills.…”
Section: Existing Researchmentioning
confidence: 94%
See 4 more Smart Citations
“…With regard to validity, multidimensional item factor analyses applied to the original multicountry validation sample revealed evidence of construct validity of the CREDI's long form. 11 In particular, a fourfactor model with item cross-loadings was found to be the best fit for the data. This work not only suggests that the CREDI is appropriately able to capture the four distinct but correlated domains of children's motor, language, cognitive, and social-emotional functioning but also demonstrates the broader utility of multidimensional scoring approaches that allow for the fact that young children's behaviors are often reflective of multiple underlying skills.…”
Section: Existing Researchmentioning
confidence: 94%
“…First, studies have shown robust evidence for the internal consistency of the CREDI's short-and long-form scores, with Cronbach's alpha values typically hovering around 0.80. 10,11,[15][16][17] Second, evidence from a subset of participants and settings has shown evidence for the CREDI's testretest reliability over an approximately 7-to 10-day period. 10,11 Indeed, sufficient stability in participant responses was considered a criterion for individual items' inclusion in the final version of the CREDI.…”
Section: Existing Researchmentioning
confidence: 99%
See 3 more Smart Citations